Quantifying the low bias of CALIPSO's column aerosol optical depth due to undetected aerosol layers. Issue 2 (20th January 2017) - Kim, Man‐Hae; Omar, Ali H.; Vaughan, Mark A.; Winker, David M.; Trepte, Charles R.; Hu, Yongxiang; Liu, Zhaoyan; Kim, Sang‐Woo
Abstract: The Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP) data processing scheme only retrieves extinction profiles in those portions of the return signal where cloud or aerosol layers have been identified by the CALIOP layer detection scheme. In this study we use 2 years of CALIOP and Moderate Resolution Imaging Spectroradiometer (MODIS) data to quantify the aerosol optical depth of undetected weakly backscattering layers. Aerosol extinction and column‐averaged lidar ratio is retrieved from CALIOP level 1B (version 4) profile using MODIS aerosol optical depth (AOD) as a constraint over oceans from March 2013 to February 2015. To quantify the undetected layer AOD (ULA), an unconstrained retrieval is applied globally using a lidar ratio of 28.75 sr estimated from constrained retrievals during the daytime over the ocean. We find a global mean ULA of 0.031 ± 0.052. There is no significant difference in ULA between land and ocean. However, the fraction of undetected aerosol layers rises considerably during daytime, when the large amount of solar background noise lowers the signal‐to‐noise ratio. For this reason, there is a difference in ULA between day (0.036 ± 0.066) and night (0.025 ± 0.021). ULA is larger in the northern hemisphere and relatively larger at high latitudes. Large ULA for the polar regions is strongly related to the cases where the CALIOP level 2 product reports zero AOD. This study provides an estimate of the complement of AOD that is not detected by lidar and bounds the CALIOP AOD uncertainty to provide corrections for science studies that employ the CALIOP level 2 AOD. Key Points: Global mean (median) lidar ratio for undetected layers is found as 32.62 (28.75) sr from the MODIS AOD‐constrained retrieval Global mean ULA retrieved using the lidar ratio of 28.75 sr is 0.031 ± 0.052 ULA is very sensitive to the lidar ratio which a significant source of error